Dinamika Kemiskinan Di Pulau Madura: Faktor Ekonomi Dan Sosial - Ifa, Khoirul; Setyo Liyundira , Fetri; Tri Indrianasari, Neny; Roos Ana, Selvia (Relasi : Jurnal Ekonomi, 2024)
Indonesia is a developing country that has tremendous poverty problems. The government does not yet have effective policies and approaches to overcome poverty as a whole in some areas such as Madura Island even though there have been development programs such as the Suramadu Bridge, which can connect Surabaya and Madura, with the hope of alleviating poverty problems on Madura Island. This study aims to analyze the effect of economic and social factors in the form of the effect of economic growth on poverty, the effect of education on poverty, the effect of health on poverty, the effect of unemployment on poverty. This study uses panel fund regression analysis, which is a combination of cross section and time series data, involving 4 districts on Madura Island, namely Bangkalan Regency, Pamekasan Regency, Sampang Regency and Sumenep Regency and observations from 2012-2023. Based on the results of the study, it is known that economic growth has a negative effect on poverty on the island of Madura, education has a negative effect on poverty on the island of Madura, health has a positive effect on poverty on the island of Madura, unemployment has a positive effect on poverty on the island of Madura.